FORTIFIKASI TEPUNG DAUN KELOR (Moringa oleifera) PADA COOKIES TEPUNG SUKUN (Artocarpus altilis) SEBAGAI MAKANAN TAMBAHAN UNTUK IBU HAMIL KURANG ENERGI KRONIS DAN ANEMIA GIZI BESI - Allice Steffi Elena Gabriela (2021)
Nutritional problems that are common in pregnant women include chronic energy starvation and iron deficiency anemia, which are caused by inadequate intake of energy, protein, and iron during pregnancy. The purpose of this study was to analyze the nutritional value, iron content, physical properties and organoleptic properties and to determine the formula chosen for breadfruit biscuits enriched with moringa oleifera leaf meal as an additional food for pregnant women with chronic energy deficiency and iron deficiency anemia. Iron. This study used a fully randomized, one-factor, two-replicate design method. These factors are the proportion of breadfruit flour and moringa leaf flour, namely F1 (60g: 40g), F2 (50g: 50g) and F3 (40g: 60g). The ANOVA test results showed no significant effect (p> 0.05) on fat content, while there was a significant effect (p <0.05) on moisture, ash, protein, carbohydrate, iron and hardness content . The Kruskal Wallis test results showed no significant effect (p> 0.05) on the degree of preference for color, texture and aroma, while there was a significant effect (p <0.05) on the degree of taste preference. The selected formula is obtained from the exponential comparison method (MPE), namely the F3 formula. The serving size of the selected biscuit formula is an energy content of 499 kcal, 8.8 grams of protein, 30 grams of fat, 45 grams of carbohydrates, 6.7 mg of iron and 5.45 N degree of hardness.